High sensitivity optical detection method based on photon RF oscillator - Ning MU; Wanrong GAO; Wanghan LYU (Tongxin xuebao)
Based on the research of optical coherent detection in complex background, a new type of laser superheterodyne detection method was proposed, which based on a photon radio frequency technology. Firstly a system by photon RF oscillation mechanism and mathematical model was constructed. The principle of constructing the system was deduced and analyzed. The correctness of the method was verified by theoretical simulation and experiment. Compared with the traditional technology, the proposed method can improve the sensitivity of optical detection by several orders of magnitude, and can effectively suppress the influence of background dispersion spectrum on target information detection.